Applying an Age-specific Definition to Better Characterize Etiologies and Outcomes in Neonatal Acute Liver Failure. Issue 1 (July 2021) - Borovsky, Kristin; Banc-Husu, Anna M.; Saul, Samantha A.; Neighbors, Katie; Kelly, Susan; Alonso, Estella M.; Taylor, Sarah A.
ABSTRACT: Objective: Neonatal acute liver failure (ALF) is a rare disease with high mortality for which no standard age-specific definition exists. To advance the understanding of neonatal ALF, we characterize the etiology, presenting features, treatment, and outcomes in infants within 1 month of life. Methods: We performed a single-center 11-year retrospective chart review of neonates ⩽30 days of life with ALF as defined by an INR of ≥2.0. Comparisons were made by etiology and survival with native liver (SNL). Estimated survival was performed using the Kaplan-Meier method. Results: Forty-three patients met inclusion criteria for neonatal ALF. Etiologies included viral infection (23%), gestational alloimmune liver disease with neonatal hemochromatosis (GALD-NH) (21%), cardiac-associated ischemia (16%), other ischemia (14%), genetic etiologies (9%), Trisomy 21-associated myelodysplasia (TAM) (7%), hemophagocytic lymphohistiocytosis (HLH) (2%), and not identified (7%). Infants with viral etiologies had the highest alanine aminotransferase (ALT) at presentation (1179 IU/L, interquartile range [IQR] 683–1585 IU/L) in contrast to low levels in GALD-NH (23 IU/L, IQR 18–64 IU/L). Across all etiologies, only 33% were alive at 1 year. Overall median survival was 74 days; 17 days for viral infection and 74 days for GALD-NH. Among laboratory values at presentation, alpha-fetoprotein (AFP) was significantly higher in patients that survived with their native liver ( P = 0.04). Conclusions: Overall, outcome for neonatal ALF is poor. Although initial laboratory values can differentiate viral infection or GALD-NH, further studies are needed to identify laboratory parameters that predict SNL by etiology to ultimately improve patient outcomes.